El análisis heurístico en la experiencia del usuario (UX)del sitio web de la Facultad de Administración Finanzas e Informática. - Arteaga Caice, Kleber Eduardo (2023)
This case study focuses on the website of the Faculty of Administration, Finance and Informatics and its heuristic analysis of the user experience, which is essential to address usability problems. This systematic and structured approach has identified UX issues such as confusing information architecture, lack of device responsiveness, inefficient internal link management, and lack of search mechanisms. Identifying these problems was the first step where this research focused. The overall goal of this research is to address user experience issues on the faculty website to improve navigation and information dissemination. A quality user experience is essential to attracting students, faculty and staff, as well as retaining their attention. The heuristics focus on aspects such as clarity of information, effectiveness of links and buttons, and consistency of design. By improving usability, you make the website more attractive and easy to use, which increases user satisfaction. The user experience is based on the smooth interaction, aesthetics and accessibility of the website. It is essential to influence visitor perception and encourage retention, engagement and loyalty to the site. Ultimately, user experience is not just about functionality, but also about the emotions, comfort, and satisfaction that users experience when interacting with the website. Heuristic analysis, as described in the heuristic evaluation guide by Hassan Montero, Yusef Martín Fernández and Francisco J. García Peñalvo, is a suitable tool to address these usability challenges and improve the website.